Endovascular treatment of carotid artery stenosis: evidences from randomized controlled trials and actual indications - Federica Ilardi; Fabio Magliulo; Giuseppe Gargiulo; Gabriele Giacomo Schiattarella; Giuseppe Carotenuto; Federica Serino; Marco Ferrone; Emanuele Visco; Fernando Scudiero; Andreina Carbone; Cinzia Perrino; Bruno Trimarco; et al. (Monaldi Archives for Chest Disease, 2015)
Atherosclerotic stenosis of common and internal carotid arteries is a well-recognized risk factor for ischemic stroke, and revascularization has been proven to be the main tool of prevention, particularly for patients with stenosis- related symptoms. While for many years surgical carotid endarterectomy (CEA) has been considered the gold-standard strategy to restore vascular patency, recently the endovascular treatment through percutaneous angioplasty and stent implantation (CAS) has become a valid alternative. In the last years, interesting data about the comparison of these strategies have emerged. CAS seems to cause more peri-procedural strokes, but may also avoid many adverse events related to surgery and general anaesthesia, including peri-procedural myocardial infarction. For these reasons, it was initially considered a second-choice strategy to be adopted in patients for whom surgery was contraindicated. However, more recent trials have shown that CAS might be considered an effective alternative to CEA. Moreover, the rapid evolution of CAS technique and materials suggests its potential to improve outcome and possible superiority compared to CEA in the next future. Purpose of this review is to discuss the most recent clinical evidences concerning the treatment of carotid artery stenosis, with a special focus on the endovascular treatment.